Improvement of hypertension after parathyroidectomy of patients suffering from primary hyperparathyroidism - Broulik, P D; Brouliková, A; Adámek, S; Libanský, P; Tvrdoň, J; Broulikova, K; Kubinyi, J (International journal of endocrinology, 2011)
Background. Primary hyperparathyroidism (PHPT) is one of the most common endocrine conditions and is accompanied by hypertension and increased cardiovascular mortality. The purpose of this study was to evaluate the effect of parathyroidectomy on systolic and diastolic blood pressure (BP) in hypertensive patients with PHPT and whether hypertension occurs more frequently in PHPT than in control group. Methods. A total of 1020 patients with proved PHPT who underwent surgery were compared with with 1020 age, sex, BMI, and smoking status matched controls. We evaluated changes in serum calcium, parathyroid hormone (PTH), uric acid, and BP before and 6 months after surgery. Results. Parathyroidectomy corrected PHPT and resulted in a substantial fall in both mean systolic (150 ± 3.8 to 138 ± 3.6 mmHg) and mean diastolic pressures (97 ± 3 to 88 ± 2.8 mmHg) of the hypertensive subjects; P < .01. In these patients, PTH, calcium, and uric acid normalized. 726 patients from 1020 with PHPT (69.8%) were found to be hypertensive whilst only 489 (47.8%) from 1020 of our control group. Conclusion. Parathyroidectomy in hypertensive patients reduces systolic and diastolic BP. PHPT is accompanied by a variety of metabolic complications, which are a risk factor for hypertension, and parathyroidectomy can improve these metabolic complications.